Aplicación de contabilidad por el sistema de inventario permanente en Klc-compu de la ciudad de Cuenca, provincia del Azuay, periodo septiembre 2013 - Quito Salinas, Paulina Isabel (2015)
This research thesis entitled "APPLICATION FOR ACCOUNTING SYSTEM OF PERMANENT INVENTORY OF KLC-COMPUTER OF THE CITY OF CUENCA, AZUAY PROVINCE; PERIOD SEPTEMBER 2013”, it was made with the aim of developing accounting practice application according to business needs, whose business lacks an adequate accounting system where inventory control of merchandise is carried efficiently, considering the Generally Accepted Accounting Principles. Note that this work was prepared in compliance with Regulation of Academic System of the National University of Loja, career of Accounting and Auditing. The objectives in KLC –COMPU is reached satisfactorily, the application of accounting by the perpetual inventory system allowed to know the stock of real goods, through the registration of the articles in Kardexs cards for all purchases and sales made as well as to obtain reasonable and reliable financial statements of the economic situation of the business; and that through the organization of the source, the plan structuring manual accounts and documents could develop the accounting process, to finally make the accounting entries relating to value added tax and income tax source. After the implementation of accounting, profit was determined, being the reflection of the result in the financial statements, and that will allow the owner to make sound decisions about investment and increase its capital in the business